(untitled) - Juan Camilo Vargas-Zambrano (Memórias do Instituto Oswaldo Cruz., 2013)
Astrocytes play a vital role in neuronal protection, homeostasis, vascular interchange and the local immune response. Some viruses and parasites can cross the blood-brain barrier and infect glia. Trypanosoma cruzi, the aetiological agent of Chagas disease, can seriously compromise the central nervous system, mainly in immune-suppressed individuals, but also during the acute phase of the infection. In this report, the infective capacity of T. cruzi in a human astrocyte tumour-derived cell line was studied. Astrocytes exposed to trypomastigotes (1:10 ratio) produced intracellular amastigotes and new trypomastigotes emerged by day 4 post-infection (p.i.). At day 6 p.i., 93% of the cells were infected. Using flow cytometry, changes were observed in both the expression of major histocompatibility complex class I and II molecules and the chemokine secretion pattern of astrocytes exposed to the parasite. Blocking the low-density lipoprotein receptor on astrocytes did not reduce parasite intracellular infection. Thus, T. cruzi can infect astrocytes and modulate the immune response during central nervous system infection.